2016
DOI: 10.1037/hea0000395
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic coping and inflammation in the context of chronic stress.

Abstract: Positive dyadic coping is a specific interpersonal process that may modulate systemic inflammation among individuals exposed to chronic stress. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…Similarly, studies on relational outcomes have consistently suggested benefits of DC. In Western couples DC has been associated with increased relationship satisfaction in parents raising Autistic children (Gouin et al, 2016) and better partner acceptance and relationship satisfaction in women with breast cancer (Zimmermann et al, 2010). When a partner is diagnosed with PTSD, low discrepancies between partners' DC also predict better relationship satisfaction regardless of the severity level of the PTSD (Witkovsky and Braakmann, 2015).…”
Section: Overall DC (Stm)mentioning
confidence: 99%
“…Similarly, studies on relational outcomes have consistently suggested benefits of DC. In Western couples DC has been associated with increased relationship satisfaction in parents raising Autistic children (Gouin et al, 2016) and better partner acceptance and relationship satisfaction in women with breast cancer (Zimmermann et al, 2010). When a partner is diagnosed with PTSD, low discrepancies between partners' DC also predict better relationship satisfaction regardless of the severity level of the PTSD (Witkovsky and Braakmann, 2015).…”
Section: Overall DC (Stm)mentioning
confidence: 99%
“…A considerable amount of studies investigating dyadic coping and relationship outcomes have been published in the past two decades. Dyadic coping has been linked to higher levels of relationship satisfaction [4], relationship stability [10], and partners individual well-being [3,5,11] better psychological adjustment to chronic stress (e.g., medical illness) [12,13] and PLOS ONE better physiological stress responses, such as cortisol recovery and increased immune reactivity [14][15][16].…”
Section: Dyadic Coping and Relationship Satisfaction: Between-and Witmentioning
confidence: 99%
“…We also tested whether personal-project-related dyadic coping strategies can be broadly described as positive and negative dyadic coping. Conceptualizations of the Systemic Transactional Model and empirical studies regularly differentiate between positive and negative dyadic coping (Bodenmann et al 2006(Bodenmann et al , 2009Papp and Witt 2010), while recent models have primarily referred to summed scores of the full scale (e.g., Gouin et al 2016;Meier et al 2011;Vaske et al 2015; for a review of prior findings using summed dyadic coping, see Falconier et al 2015). In the present study, based on factor analysis explorations we calculated the overall scores for positive and negative dyadic coping experiences of the partners' merging of self-and partner evaluations.…”
Section: Analytical Processmentioning
confidence: 99%